2019
DOI: 10.12955/cbup.v7.1353
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Economic Management in the Regions of Kazakhstan to Ensure Environmental Safety

Abstract: This article describes the objectives and methods of ecological environment management and sustainable environmental management at the regional level and with the impact of economic instruments. The optimum solutions to environmental management problems with a view to preserving natural resources and the reduction of risk of harm to the ecological environment were examined. Based on the analysis of conceptual approaches to the formation of the economic mechanism for ensuring environmental safety, the fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Limited technology in oil extraction in these regions has resulted in increased pollution with hydrocarbons, surfactants, and heavy metals. Igaliyeva [18] showed that chloral organic pesticides and phenol. Primarily, petroleum hydrocarbons are responsible for changing the morphological, physiological and biochemical structure of organisms and physical environment, which are irreversible and cause chronic pathological effects.…”
Section: Marine Environmental Pollution Due To Petroleum Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited technology in oil extraction in these regions has resulted in increased pollution with hydrocarbons, surfactants, and heavy metals. Igaliyeva [18] showed that chloral organic pesticides and phenol. Primarily, petroleum hydrocarbons are responsible for changing the morphological, physiological and biochemical structure of organisms and physical environment, which are irreversible and cause chronic pathological effects.…”
Section: Marine Environmental Pollution Due To Petroleum Hydrocarbonsmentioning
confidence: 99%
“…Igaliyeva [17] demonstrated, the rivers such as Amudarya, Syrdarya are fed through these glaciers and hence they are also being shrieked day by day. Glaciers are being melted due to an increase in toxic dust causing precipitation and mineralisation of glaciers.…”
Section: Nature-society Linkage In the Vicinity Of Aral Seamentioning
confidence: 99%